Konstruksi Kewenangan Direktorat Jenderal Pajak Atas Pengelolaan Barang Sitaan Pajak yang Gagal Dilelang Berulang Kali - Aerolla, Grevitha; Permadi, Haru; Rahmawan, Triya Indra (RechtJiva, 2026)
Tax revenue constitutes 83.34% of Indonesia's total state income in 2025, making the effectiveness of tax collection a crucial factor for national financing. The seizure of taxpayer assets subsequently sold through public auction represents one of the strongest collection instruments available. However, data indicates that auction success rates remain low and no existing legal provision governs the fate of seized assets that repeatedly fail to sell at auction as the statute of limitations approaches. This study aims to formulate an ideal legal construction governing the authority of the Directorate General of Taxes (DGT) in managing tax-seized assets that repeatedly fail to sell at auction prior to the expiration of the collection statute of limitations, and to determine the most appropriate form of legislation through which such authority should be established. This study employs a normative juridical method with statute, conceptual, and case approaches, analyzed through legal discovery techniques. The findings indicate that the ideal legal construction is the granting of authority to the DGT to manage seized assets that fail to sell after three auction attempts by adopting the asset management mechanism for excisable goods and other goods under Ministerial Regulation No. 17 of 2024, namely by transferring such assets into State-Controlled Assets and State Property. The appropriate legislative form is a three-tiered regulatory package commencing with an amendment to the Tax Collection Law through the insertion of Article 27A governing the authority of the Directorate General of Taxes, followed by a new Government Regulation governing the procedures for designating State-Controlled Assets and State Property, and an implementing Ministerial Regulation governing the technical and administrative details thereof.